Unsteady boundary layer flow of a nanofluid over a stretching/shrinking sheet with a convective boundary condition - Syahira Mansur; Anuar Ishak (Journal of the Egyptian Mathematical Society, 2016)
The unsteady boundary layer flow of a nanofluid past a stretching/shrinking sheet with a convective surface boundary condition is studied. The effects of the unsteadiness parameter, stretching/shrinking parameter, convective parameter, Brownian motion parameter and thermophoresis parameter on the local Nusselt number are investigated. Numerical solutions to the governing equations are obtained using a shooting method. The results for the local Nusselt number are presented for different values of the governing parameters. The local Nusselt number decreases as the stretching/shrinking parameter increases. The local Nusselt number is consistently higher for higher values of the convective parameter but lower for higher values of the unsteadiness parameter, Brownian motion parameter and thermophoresis parameter.